“Please learn from my mistakes”: the acute need for an entrepreneurial mindset in academic biosensor research - Heikenfeld, Jason (Frontiers in Sensors, 2024)
History is full of technological breakthroughs that arguably were first discovered because fundamental research was conducted without commercial influence. Fundamental research also plays an important role in producing the next generation of researchers. However, this article argues that research in general, and particularly biosensor research, is suffering from diminishing impact because of a lack of entrepreneurial mindset when defining research objectives. The story of the author’s own biosensor research pathway is presented, and it provides an exemplary case study of this larger problem. An entrepreneurial mindset enables a stronger foundation even at the stage of forming the research hypothesis: the need for the research is justified; the research is not duplicative and is positioned to create new knowledge; the research product will be more readily translatable by industry. Most graduates in sensor research will work in industry, and therefore those students exposed to an entrepreneurial mindset will also start their careers with a more complete set of the skills that industry is looking for.